mm-Wave silicon technology : 60GHz and beyond - Niknejad, Ali M., 1972-; Hashemi, Hossein (New York : Springer Science+Business Media, 2008)
"mm-Wave Silicon Technology: 60GHz and Beyond covers silicon-based millimeter wave circuits and systems. It provides in depth coverage of advanced silicon processing technologies including CMOS and SiGe as well as modeling of active and passive devices on silicon at millimeter waves. It also provides coverage of mm-wave circuit building blocks such as low noise amplifiers, mixers, voltage controlled oscillators, frequency dividers, and power amplifiers that are suitable for integration in silicon. The book contains information on highly integrated mm-wave transceiver architectures with several silicon-based case studies. The book also includes advanced topics such as antenna arrays and beam-forming on silicon." "mm-Wave Silicon Technology: 60GHz and Beyond is written for practicing RF and analog circuit designers who are interested in this growing field. The chapters are self-contained and include short tutorials on important concepts before delving into details."--BOOK JACKET.
Cover -- TOC-- Contents -- CH. 1. Introduction to mm-Wave Silicon Devices, Circuits, and Systems -- 1.1 Introduction -- 1.2 Whymm-Waves? -- 1.3 The Birth of Silicon mm-Wave -- 1.3.1 Why CMOS? -- 1.3.2 True Cost of Silicon mm-Wave -- 1.4 Communication in the 60 GHz Band -- 1.4.1 BeamForming -- 1.5 Uniquemm-WaveApplications -- 1.5.1 mm-Wave Spectrum -- 1.5.2 Automotive Radar -- 1.5.3 mm-Wave Imaging forMedicalApplications -- 1.5.4 Collaborative DistributedMIMO -- 1.6 Overview of Book -- References -- CH. 2. Silicon Technologies to Address mm-Wave Solutions -- 2.1 Why Silicon? -- 2.1.1 Performance -- 2.1.2 Cost, Integration [3] -- 2.1.3 ManufacturingCapacity -- 2.2 Modern SiGe and CMOS Technology -- 2.2.1 Lithography -- 2.2.2 Low-K Dielectrics and CopperWiring -- 2.2.3 Mobility and Strain Engineering -- 2.2.4 Metal Gates &High-K Dielectrics -- 2.3 Active Devices on Recent Bulk and SOI Technologies -- 2.3.1 Bipolar Devices -- 2.3.2 CMOS devices -- 2.3.3 SOI CMOS devices -- 2.3.4 Current Density Scaling for CMOS and Bipolar Devices -- 2.3.5 Comparison Between State-of-the-Art HBT and CMOS Devices -- 2.4 Impact of the Back-End of Line onmm-WaveDesign -- 2.5 Conclusion -- 2.6 Acknowledgements: -- References -- CH. 3. Design and Modeling of Active and Passive Devices -- 3.1 Passive Devices -- 3.1.1 Transmission Lines -- 3.1.2 Inductors -- 3.1.3 Capacitors -- 3.1.4 Transformers -- 3.1.5 Resonators -- 3.2 Active Devices -- 3.2.1 Modeling -- 3.2.2 Active Device Design -- 3.2.3 Small-SignalModel -- 3.2.4 Large-SignalModel -- 3.2.5 FET NoiseModel -- 3.3 Conclusion -- References -- CH. 4. Amplifiers and Mixers -- 4.1 60GHz Low-NoiseAmpli.ers:What's Different? -- 4.1.1 Transistors Closer to Cutoff -- 4.1.2 SmallWavelengths -- 4.1.3 Parasitics at 60 GHz -- 4.2 Low-NoiseAmplifier Design Methodology -- 4.2.1 Input Match Optimization for Noise and Power -- 4.2.2 Transistor Noise Parameters -- 4.2.3 Common-Base vs. Common-Emitter -- 4.3 Low-NoiseAmpli.er Examples -- 4.3.1 Bipolar LNA (v1), Common-Base Input -- 4.3.2 Bipolar LNA (v2), Common-Emitter Input -- 4.3.3 CMOS Common SourceAmpli.ers -- 4.3.4 CMOS CommonGateAmplifiers -- 4.3.5 Differential PairAmplifiers -- 4.3.6 Multi-Stage Amplifier Design -- 4.3.7 ATwo-Stage 30 GHzAmplifier -- 4.4 Mixers and FrequencyTranslation -- 4.4.1 Single TransistorMixers -- 4.4.2 Dual GateMixers -- 4.4.3 Gilbert CellMixers -- 4.5 Examples of Integrated Front-Ends -- 4.5.1 CMOS 130nm 60 GHz Front-End -- 4.5.2 SiGe Transceiver Chipset -- 4.6 Conclusion -- References -- CH. 5. Voltage-Controlled Oscillators and Frequency Dividers -- 5.1 Considerations ofVCOs -- 5.2 Cross-Coupled Oscillators -- 5.
engineering bookfair2015
Includes bibliographical references and index.
Keywords: Millimeter wave communication systems; Millimeter wave devices -- Design and construction; Integrated circuits -- Materials; Silicon -- Electric properties